Study guides

☆☆

Q: X2 plus 5x plus 6 how to solve?

Write your answer...

Submit

Still have questions?

Related questions

x2 + 5x + 6 = (x + 2)(x + 3)

x2 - 5x + 6 = (x - 2)(x - 3)

x2 + 5x + 3 = 9 x2 + 5x - 6 = 0 (x + 6)(x - 1) = 0 x = -6 or x = 1

x2+5x+6 = (x+2)(x+3)

x2+5x-6 = (x+6)(x-1) when factored

x2 + 5x - 6 = x2 + 6x - x - 6 = x(x + 6) - 1(x + 6) = (x - 1)(x + 6)

x(x2+5x+6)

=(x+3)(x+2)

(x-6)(x+1)

x2-5x-6 = (x-6)(x+1)

x2 - 5x -6 = (x-6)(X+1)

x - 3

This is not possible to answer without knowing if it is "plus 6", "minus 6", or "equals 6".

5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5

If you mean: x2+5x+6 = 0 then the solutions are x = -3 and x = -2

(x - 3)(x - 2)

x2 + 5x =6 x2+5x -6 = 0 (x+6)(x-1) = 0 x+ 6 = 0 x = -6 x-1 = 0 x = 1

x3 + 4x2 + x - 6 = 0 x3 - x2 + 5x2 - 5x + 6x - 6 = 0 x2(x - 1) + 5x(x - 1) + 6(x - 1) = 0 (x - 1)(x2 + 5x + 6) = 0 (x - 1)(x + 2)(x + 3) = 0 So x = 1 or x = -2 or x = -3

5x+2 = 3x-6 5x-3x = -6-2 2x = -8 x = -4

You don't factor an equation. You factor an expression.So we'll forget about the "equals 0" for a second, while we factor "x2 plus 5x plus 6".x2 + 5x + 6 = (x + 3) (x + 2).Now, if you want this expression to be equal to zero, that can only happen when 'x' is -2 or -3.

x2 - 5x - 6 = x2 - 6x + x - 6 = x(x - 6) + 1(x - 6) = (x - 6)(x + 1)

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

The vertex of x2 - 5x + 6 is (2.5, -.25). (This can be solved with calculus: Take the derivative of x2 - 5x + 6, which is 2x- 5. Then set it equal to zero to get the x value: 2x - 5 = 0, so x = 2.5. Plug this value back into x2 - 5x + 6 to get the y value: -.25. In pre-calculus, this is normally done by using a graphing calculator instead.)

x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2

x3 + 12x2 - 5x = x(x2 + 12x - 5) = x(x + 6 - √41)(x + 6 + √41)